Adalimumab Therapy Restores the Gut Microbiota in Patients With Ankylosing Spondylitis - Chen, Zena; Zheng, Xuqi; Wu, Xinyu; Wu, Jialing; Li, Xiaomin; Wei, Qiujing; Zhang, Xi; Fang, Linkai; Jin, Ou; Gu, Jieruo (Frontiers in Immunology, 2021)
Growing evidence suggests that the gut microbiome is involved in the initiation and progression of ankylosing spondylitis (AS). In this study, we aimed to explore alterations in the gut microbiome that occur during adalimumab therapy and their relationship with the treatment response. We evaluated the gut microbial features of 30 patients with AS who received adalimumab treatment for 6 months and 24 healthy controls. We confirmed that the microbiome was restored significantly after 6 months of adalimumab therapy in AS patients. We then compared the baseline gut microbiome of adalimumab responders to that of non-responders and observed a higher abundance of Comamonas in the non-response subgroup, although no significant differences were found after adjusting for the false discovery rate. These results suggest that adalimumab therapy restored the gut microbiome in patients with AS and indicate the utility of the gut microbiome as a possible prognostic tool. These findings may contribute to the development of predictive tests suitable for clinical practice and the establishment of precise medical interventions.